Evaluasi Program-program Pengentasan Kemiskinan di Provinsi Bali - AAIN Marhaeni; Ketut Sudibia; IGAP Wirathi; Surya Dewi Rustariyuni; Putu Martini Dewi (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2014)
The success of the development carried out by a country, including Indonesia, one of which can be seen from the number of poor people. The results of the development carried out by both the local government and the central government still leaving the poverty in most of the existing population. The number of poor people in the Province of Bali, both in absolute and in the percentage is fluctuating, even absolutely, the number of poor people in 2011 was much more than in 2009 (183.1 thousand versus 173.6 thousand of people). It is essential to evaluate the government programs to be in accordance with the Act Number 25 Year 2004 on National Development Planning System which mandates the control and evaluation of the implementation of development plans and to be in accordance with the Government Regulation. 39 of 2006, concerning the monitoring. Seeing the importance of activities to perform the evaluation or monitoring, the study aims: 1) to determine the effectiveness of poverty eradication programs that have been implemented by the government so far, which is reducing the expenditure of the poor people, which involving inputs, processes and outputs;2) To analyze the constraints faced by the implementers in the implementation of poverty eradication programs that are reducing the expenditure of the poor; 3) To assess the benefits perceived by the recipients of the program, during receiving aids in the areas of education, health, and food sector; 4) to analyze the weaknesses that exist in the various poverty eradication programs that have been implemented by the government; 5) to assess the commitment of the program implementers in implementing poverty eradication programs in accordance with the community expectations. The research was conducted in three regencies, namely Buleleng, Badung, and Klungkung and each consisted of as many as 90 persons including the recipients of poverty eradication programs in the fields of education, health, and, food, as well as the informants. Thus the total number of respondents and informants were as many as 270 people in the three regencies. The sampling method used both for the respondents of program recipients and for the informants was purposive sampling combined with accidental sampling. The data collection method was conducted by a variety of methods: observation, interviews, and in-depth interviews. Before the data collection was done, the test of validity and reliability tests were conducted on the research instruments to be used in collecting the data. The analysis technique used was the descriptive statistical techniques both single-frequency distributions and cross-tabulations. It was also conducted the qualitative or descriptive analysis based on the results obtained from the in-depth interview of the informants and the respondents. Overall, the effectiveness of aid programs in the field of food aid, particularly aid of rice for the poor is lesser compared with the effectiveness of the other two aids, namely in the areas of education and health. The recipients of food aids especially those who received rice for the poor gained less benefits from the aids given. The problem faced in the real situation, namely prior to the distribution of aids, the village meetings (Muskel and Musdes) were not conducted in a timely manner so that the data received from the central government to be used as the basis for the distribution of rice for the poor become less accurate. Weaknesses faced by the program in its implementation, among others, the implementation of data collection that is considered to be too long so that its target is inaccurate especially the distribution of the rice aids for the poor.